A healthy lifestyle app for older adults with diabetes and hypertension: usability assessment. (2017) - Smith-Turchyn, Jenna; Gravesande, Janelle; Agarwal, Gina; Mangin, Dee; Javadi, Dena; Peter, Jessica; Parascandalo, Fiona; Dolovich, Lisa; Richardson, Julie
Risk factor modification interventions using mobile health technology have been shown to be effective in managing non-communicable lifestyle related conditions. The objective of this study was to explore how older adults with type 2 diabetes and hypertension use an online app developed to help manage these conditions. Usability testing was conducted on the TAPESTRY-CM Healthy Lifestyle App, an online self-management application. This included an online session, using a cognitive interviewing approach, and semi-structured interviews at various times. Qualitative content analysis was performed as sessions were completed using coding and category formation. All participants commented positively on app content. Suggestions for improvement were given in regard to app content and layout. This study provides strong support for initial use of this app. Results of this study will be used to improve the app prior to conducting larger scale effectiveness trials or using it in clinical practice.